Produção de mudas de oliveira em sistemas de cultivo sem solo - Cappellaro, Thais Helena (2013)
The propagation and growth of cv. Arbequina olive cuttings were studied at different epochs, concentrations of growth regulator, environment material collection and cultivation systems, along with the maintenance and rooting of cuttings from mother plants through three experiments conducted in greenhouse and plastic greenhouse Campus Didactic and Experimental Universidade Federal de Pelotas. The experiment 1 was conducted to evaluate the most appropriate epoch for rooting, the influence of the environment where the plants were located arrays and the effect of different concentrations of IBA (IBA) on rooting semihardwood cuttings of olive, Arbequina cultivar. Rooting was tested in three epochs (winter, spring and summer), collecting material environment (greenhouse and open field) and five concentrations of IBA (0, 1000, 2000, 3000 and 4000 mg l-1). The minicuttings were collected and standardized with two pairs of buds and leaves a pair of socks and subsequently placed for rooting in plastic boxes with average particle size of vermiculite, after preparation were placed in a greenhouse with controlled temperature of 25 ± 2 ° C for 80 days in three epoch. The evaluated variables were: percentage of minicuttings survival, percentage of rooted minicuttings, number of roots per minicutting and length of the roots. Minicuttings coming greenhouse provide greater survival, rooting number and root length. Spring is the epoch that, regardless of the collection environment, provide greater survival, rooting, number and length of roots. The use of material from open field and regulator at 3000 mg.L-1 provides greater rooting. Material collected in spring subjected to concentrations of 3000 and 4000 mg.L-1 produce greater number of roots. The experiment 2 was conducted to evaluate the growth of olive seedlings obtained by minicutting Arbequina cultivar in soilless systems and at different epoch. The rooted minicuttings were placed to grow in three systems (semi-hydroponic, NFT -Nutrient Film Technique- and conventional ), in two epochs (fall / winter and spring / summer) for five months of cultivation. In the semi-hydroponic system substrate used was sand and irrigated daily with nutrient solution. In NFT the cuttings were placed in phenolic foam which were irrigated through intermittent flow and in the conventional plants were grown in plastic bags filled with a substrate Carolina ®, being provided 100ml of nutrient solution every 15 days. The variables analyzed were: number of shoots, shoot length, number of secondary shoots and secondary shoots length during the growing season and after 150 days of cultivation variables analyzed were: stem diameter, fresh and dry weight of shoots, fresh and dried root. The use of semi-hydroponic system provides greater plant growth. The epoch of greatest light intensity provides greater plant growth. The use of semi-hydroponic system and epoch 2 of warmer temperatures (spring / summer) provide increased plant growth. The experiment 3 was to evaluate the rooting of olive minicuttings from mother plants packed in soilless systems and conventional and assess the nutrient content of these minerals mother plants in two cropping epochs (fall / winter and spring / summer). The plants were in three cropping systems which were described in the second experiment. The minicuttings were collected in winter and set to root as the first experiment, but the IBA concentration was 3000 mg.L-1. The variables analyzed after 80 days were: percentage of minicuttings survival, percentage of minicuttings, number of roots per minicuttings, length of roots and for the analysis evaluated the nutritional content of macronutrients and micronutrients and dry mass of shoots and the root. The use of material from headquarters in soilless systems and conventional not differ in rooting of cuttings in winter. The semi-hydroponic system at epoch 2 (spring / summer) achieved higher levels of nutrients. In epoch 2 the semi-hydroponic system produces higher dry mass´´ content of shoot and root